(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
В О с н о в у Р а б о т ы П о л о ж е н ы Д а н н ы е О б с л е д о в а н и я 2 4 4 Б о л ь н ы х И з Ю ж н ы х Р е г и о н о в Р е с п у б л и к и У з б е к и с т а н , К о т о р ы е П о л у ч и л и Л е ч е н и е В Ц е н т р а х Ф т и з и а т р и и И П у л ь м о н о л о г и и В П е р и о д е С 2 0 1 6 П о 2 0 2 0 Г г